An ED patient with low testosterone. Issue 5 (September 2016) - Hackett, Geoffrey
Abstract : In this article, we consider the case of a patient referred to the erectile dysfunction (ED) clinic for second‐line treatment. The patient had many of the signs and symptoms of hypogonadism, but even when this was revealed his treatment pathway was not straightforward.